Atypical postictal transient subcortical T2 hypointensity in a newly diagnosed diabetic patient with seizures. Issue 3 (18th July 2018) - Paoletti, Matteo; Bacila, Ana; Pichiecchio, Anna; Farina, Lisa Maria; Rognone, Elisa; Cremascoli, Riccardo; Fanucchi, Simona; Manni, Raffaele; Bastianello, Stefano
ABSTRACT: Common postictal MRI findings include transient cortical T2 hyperintensity, restricted diffusion, and gyral and/or adjacent leptomeningeal contrast enhancement. In certain uncommon pathological conditions, other signal abnormalities can be present, suggesting a different underlying pathogenic mechanism. We report the case of a 66‐year‐old man, recently diagnosed with diabetes mellitus type 2, presenting with new‐onset visual and auditory hallucinations, "absence" seizures, and repeated peaks of hyperglycaemia without hyperketonaemia or increased serum osmolarity. EEG confirmed epileptic discharges in the right temporal region and MRI showed vast subcortical T2 hypointensity in the right temporal lobe, without any cortical hyperintensity, restricted diffusion, or contrast enhancement. Subcortical signal abnormality and EEG discharges resolved after a month of follow‐up, with a small juxtacortical gliotic focus as a sequela. Peaks in hyperglycaemia have been reported to be responsible for T2 hypointense subcortical abnormalities through a proconvulsant mechanism linked to increased ketone body concentrations. Hyperosmolarity and hyperketonaemia were not evident in this case, however, transient accumulation of free radicals that alter the intercellular space can be considered the presumable cause of this finding. In summary, it is important to consider any unusual findings on postictal MRI in order to avoid errors in interpretation.